A Comparison of Reduplication Between Patani Malay (Southern Thailand) and Indonesian - Nila Safina; Rita Rita; Ratna Soraya; Rika Kartika; Affan Topake (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research is entitled "Comparison of Indonesian Language Reduplication and Patani Malay (South Thailand)". The research problem is whether there are similarities and differences in the form of reduplication of Indonesian and Patani Malay words. The collected data will be described, analyzed and interpreted in detail in order to obtain a correct picture of the similarities and differences between Indonesian and Patani Malay reduplications. The research method used is descriptive method which is used to record and describe the reduplication of Indonesian words with Patani Malay. If language data is used without comparison with previous data and this method is used to check reduplication at a glance, then it is refined by selecting and grouping according to the form of reduplication used as a reference in comparison. The conclusion in this study is that in the form of reduplication, Indonesian and Patani Malay have similarities and differences, the differences come from phonemics and pronunciation. The similarities and differences of each form are: 1. Basic reword 2. Reword based on meaning and takes the form 3. Rewords are based on phoneme forms.